A Review of Neutron Scattering Applications to Nuclear Materials. (7th August 2013) - Vogel, Sven C.
Abstract : The growing demand for electric energy will require expansion of the amount of nuclear power production in many countries of the world. Research and development in this field will continue to grow to further increase safety and efficiency of nuclear power generation. Neutrons are a unique probe for a wide range of problems related to these efforts, ranging from crystal chemistry of nuclear fuels to engineering diffraction on cladding or structural materials used in nuclear reactors. Increased flux at modern neutron sources combined with advanced sample environments allows nowadays, for example, studies of reaction kinetics at operating temperatures in a nuclear reactor. Neutrons provide unique data to benchmark simulations and modeling of crystal structure evolution and thermomechanical treatment. Advances in neutron detection recently opened up new avenues of materials characterization using neutron imaging with unparalleled opportunities especially for nuclear materials, where heavy elements (e.g., uranium) need to be imaged together with light elements (e.g., hydrogen, oxygen). This paper summarizes applications of neutron scattering techniques for nuclear materials. Directions for future research, extending the trends observed over the past decade, are discussed.